The Clinical Application of Mealtime Whey Protein for the Treatment of Postprandial Hyperglycaemia for People With Type 2 Diabetes: A Long Whey to Go - Smith, Kieran; Bowden Davies, Kelly A.; Stevenson, Emma J.; West, Daniel J. (Frontiers in Nutrition, 2020)
Postprandial glycaemia is a major contributor to overall glycaemic control for people with type 2 diabetes, ultimately impacting the risk of microvascular and macrovascular complications associated with this disease. Mitigating postprandial hyperglycaemic excursions may be effective in not only enhancing glycaemic control but also reducing the onset of diabetes complications. There are, however, growing concerns over the long-term efficacy of traditional anti-hyperglycaemic pharmacotherapies, which coupled with their rising financial costs, underlines the need for further non-pharmaceutical treatments to regulate postprandial glycaemic excursions. One promising strategy that may improve postprandial glycaemia for people with type 2 diabetes is through the provision of whey protein beverages around mealtimes. Whey protein stimulates the secretion of insulin and the incretin peptides and delays the rate of gastric emptying, suppressing postprandial hyperglycaemia. However, evidence to date stems from study participants with clinical characteristics that do not represent the wider majority of the type 2 diabetes population, studied under strict and acute experimental conditions. The methodological approaches applied, and outcomes reported, have also been unrealistic and may not portray what is achievable in practice. The translation of these findings into everyday care is, therefore, questionable. This review will discuss acute evidence surrounding the application of mealtime whey protein to treat postprandial hyperglycaemia in individuals with type 2 diabetes and proceed to highlight experimental gaps that require addressing when considering this strategy’s clinical application to treat type 2 diabetes.